Relevance of MasLows Theory in the Modern Day Middle and Top Management - Jain, Samta; Mehta, Namrata (SFIMAR Research Review, 2016)
The paper attempts to study the relevance af Maslaw’s Need Hierarchy in modern organizations for both middle and top level management. It is based on ffie fact that a behavior arouses out of a direction given by motivation. Motives are the foundation of human behavior. In the current day context, motives of the individuals ore also influenced by the social and demographic conditions. Still we find that Mas/ow’s Need Hierarchy is applicable and can be utilized for deriving the Appraisal methods and train ing for the executives at different levels in the organization.